(untitled) (Bulletin of the International Association for Paleodontology, 2024)
Professional compatibility of dental practitioners in medico-legal practices is essential for modern healthcare, requiring alignment of competencies, ethical standards, and legal compliance to ensure effective and safe patient care. This study examines the professional and legal challenges faced by dental practitioners in Indonesia through a qualitative case study analysis of two significant dental malpractice cases adjudicated by the Supreme Court in Jakarta (2016) and Denpasar, Bali (2015). The research reviews legal documents, court rulings, and medical records, supplemented by expert consultations and comparative analysis. The findings emphasize the importance of accurate medical records, effective communication, informed consent, and adherence to professional standards. This paper highlights the implications for the Indonesian healthcare system, advocating for enhanced communication skills, continuous education, and clearer guidelines to protect patient rights and guide practitioners. These insights provide valuable lessons for improving healthcare delivery, safeguarding patient rights, and reducing medical malpractice, contributing to a more robust and patient-centric healthcare system in Indonesia.